Beyond Rhabdomyolysis: Uncommon Challenges in Clinical Practice - Mesquita, Pedro Duarte; Costa, Teresa Maria; Silva, Diogo Ferreira da; Mateus, Sofia Mohamed; Aliberti, Raffaele Junior; Galvão, Íris Simões; Vale, Luís Ferrão (International Journal of Innovative Research in Medical Science, 2025)
Paget-Schroetter Syndrome (PSS) is a rare form of upper extremity deep vein thrombosis (UEDVT), commonly associated with repetitive arm movements or anatomical abnormalities of the thoracic outlet. Due to its rarity, it can be overlooked, leading to delayed diagnosis and treatment. The authors present the case of a young healthy male, who developed right upper limb pain and swelling, following an intense calisthenic workout and an 18-hour flight. Initially diagnosed and treated for rhabdomyolysis, further evaluation revealed painful asymmetry in the right arm. A venous Doppler ultrasound and subsequent Computed Tomography (CT) venography confirmed Paget-Schroetter syndrome. This case highlights the importance of considering this rare entity, a subset of thoracic outlet syndrome, in young males presenting with post-exertional upper limb pain, particularly in the dominant arm.